Statistical quality control study Manhattan Rubber Manufacturing Corporation - Fernandez, Glenn (College of Engineering, 2000)
A quality control study is performed on Manhattan Rubber Manufacturing Corporation during the period from June to September 200. Manhattan is the largest manufacturer of bicycle and motorcycle tires in the country. It is based in Valenzuela City. Before the study is conducted the proportion of defective MC 300 tires per shift is 0.0587. 2.98 percent of these are caused by light side, 0.87 percent by ply separation, 1.06 percent by joint, and 0.48 percent can be attributed to several other causes like foreign matter, open cord, loose coupler, overflow, mechanical trouble. etc. The three main problems that are investigated are: light side, ply separation, and off-centeredness. Process capability analyses reveal that the processes involving the main problems are capable of meeting the requirements set by Manhattan, The process capability of the process due to light side is 1.1986, for the ply separation, 1.1464, for the off-centeredness, 1.1590, and for the uneven thickness of the tread, the capability ratio is 1.344. In addition, separate p-charts are constructed for each defect. It is found out that the process is under statistical control for light sider and ply separation. However, in the p-chart for off-centeredness, three points are beyond the upper control limit. Additional in depth analysis is done on this defect to find the assignable causes that can account for the outliers. The main causes identified are the operators' lack of training and unevenness of the thickness of the extruded caused by loos extruder die. The study proponents then recommend the following: provide additional training and replace the loos dies. The estimated total cost that would be incurred would amount to Php 11,500 for the replacement of each loose die. The number of defects is expected to drop to a minimum level of nonconformance, which can be as low as zero per shift. With no defective item due to off-centeredness, the cost of training is recoverable after 16 days of motorcycle tire production. However, the replacement cost is repetitive and will be incurred at the end of the useful life of an extruder die. But weighed against the savings that Manhattan will obtain everytime no off-center is made, the cost of replacement can be considered insignificant. If the target of "zero off-center" is met continuously, profit is expected to increase by Php 6,300 per day, at the minimum.